Developing deontology : new essays in ethical theory - Hooker, Brad, 1957- (Malden, MA : Wiley, Blackwell, 2012)
Developing Deontology consists of six new essays in ethical theory by leading contemporary moral philosophers. Each essay considers concepts prominent in the development of deontological approaches to ethics, and these essays offer an invaluable contribution to that development. Essays are contributed by Michael Smith, Philip Stratton-Lake, Ralph Wedgewood, David Owens, Peter Vallentyne, and Elizabeth Harman - all leading contemporary moral philosophersEach essay offers an original and previously unpublished contribution to the subjectA significant addition to the field for anyone with an inter.
Front Matter -- Deontological Moral Obligations and Non-Welfarist Agent-Relative Values / Michael Smith -- Recalcitrant Pluralism / Philip Stratton-Lake -- Defending Double Effect / Ralph Wedgwood -- The Possibility of Consent / David Owens -- Enforcement Rights against Non-Culpable Non-Just Intrusion / Peter Vallentyne -- Does Moral Ignorance Exculpate? / Elizabeth Harman -- Index.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Ethics; PHILOSOPHY -- Ethics & Moral Philosophy; Ethics; Electronic books